NUMERICAL ANALYSIS OF AERO- AND HYDROELASTIC STABILITY OF SHELLS OF REVOLUTION MADE OF FUNCTIONALLY GRADED MATERIALS - Bochkarev, S.A.; Lekomtsev, S.V.; Fedorov, A.Yu. (Perm Federal Research Centre Journal, 2017)
The results of research on the dynamic behavior of cylindrical shells made of functionally graded materials, having a circular or non-circular cross-section, have been presented. The solution of the problem, which is implemented with the use of the finite element method, is reduced to the evaluation of complex eigenvalues of the coupled system of equations. The results of numerical simulation demonstrate the influence of different factors (boundary conditions, consistencies of the examined FG-materials, fluid level, mechanical or thermal loads) on the natural frequencies and boundaries of aero- and hydroelastic stability.